TWO APPROACHES TO DOIS IRMÃOS:: SOCIOLINGUISTIC DISTANCE AND LITERARY TRANSLATION STRATEGIES (Belas Infiéis, 2015)
Using key chapters from Milton Hatoum’s Dois Irmãos (2000), we set about testing John Milton’s hypothesis (2011) that grammatically more similar languages would yield fewer adaptations in translation. Our sample, on the contrary, revealed that the sociolinguistically closer Italian translation varied more than the more distant English version, and in equidistant sociolinguistic cases involving slang and indigenous loanwords, the Italian version offered more audience-appropriate (i.e. acceptable) variations. It could be that the closeness of the languages (Portuguese-Italian), combined with the translator’s sociolinguistic understanding may, instead, have provided a platform for both more “acceptable” (freer) and more “adequate” (“equivalent”) structures.